The impact of a carbon tax on manufacturing: Evidence from microdata - Martin, Ralf; de Preux, Laure B.; Wagner, Ulrich J. (Journal of public economics, 2014)
We estimate the impact of a carbon tax on manufacturing plants using panel data from the UK production census. Our identification strategy builds on the comparison of outcomes between plants subject to the full tax and plants that paid only 20% of the tax. Exploiting exogenous variation in eligibility for the tax discount, we find that the carbon tax had a strong negative impact on energy intensity and electricity use. No statistically significant impacts are found for employment, revenue or plant exit. •First micro-econometric evidence on carbon taxation based on UK flagship policy.•Compare outcomes between plants paying full tax and those paying only 20%.•Exogenous variation in eligibility used to instrument for tax rate.•Carbon tax reduced energy intensity by 18.1% and electricity use by 22.6%.•No evidence of adverse impacts on employment, revenue or plant exit.